Numerical investigation of turbulent swirling flows through an abrupt expansion tube - S. Eiamsa-ard; P. Promvonge (ASEAN Journal on Science and Technology for Development, 2006)
A numerical investigation of turbulent swirling flows through an abrupt expansion tube is reported.  The TEFESS code, based on a staggered Finite Volume approach with the standard k-? model and first-order numerical schemes built-in, was used to carry out all the computations. The code has been modified in the present work to incorporate the ASM and two second-order numerical schemes.  The ASM, which includes the non-gradient convection terms arising from the transformation from Cartesian to cylindrical coordinates, was investigated for isothermal flows by applying it to the flow through an abrupt expansion tube with or without swirl flows.  In addition, to investigate the effects of numerical diffusion on the predicted results, two second-order differencing schemes, namely, second-order upwind and the quadratic upstream interpolation, were used to compare with the first-order hybrid scheme.  An abrupt expansion tube with non-swirling flow, predicted results using both the k-? model and the ASM were in good agreement with measurements.  For swirling flows, the calculated results suggested that the use of the ASM with a second-order numerical scheme leads to better agreement between the numerical results and experimental data, while the k-? model is incapable of capturing the stabilizing effect of the swirl.